2022
DOI: 10.1177/23259582211073399
|View full text |Cite
|
Sign up to set email alerts
|

Decision conflict and the decision support needs of HIV PrEP-eligible Black patients in Toronto regarding the adoption of PrEP for HIV prevention

Abstract: Objectives: This study examined factors contributing to decision conflict and the decision support needs of PrEP-eligible Black patients. Methods:The Ottawa Decision Support Framework (ODSF) was used to guide the development of a key informant guide used for qualitative data collection. Black patients assessed by healthcare providers as meeting the basic criteria for starting PrEP were recruited through the St. Michael's Hospital Academic Family Health Team and clinical and community agencies in Toronto. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Scoping: Assessment of Patients' and Clinicians' Views on Decisional Needs We conducted key informant interview of 29 PrEP-eligible Black patientsdifferent gender, sexual orientation, and at different decision-making stage -to understand their decision-making process and to assess their decision support needs for PrEP. The result of this phase of the development process has been reported by Ajiboye et al (12). We also surveyed 25 PrEP providers (clinical and service providers) to assess needs and preferences for a decision support tool for PrEP-eligible Black patients.…”
Section: Original Manuscriptmentioning
confidence: 90%
See 4 more Smart Citations
“…Scoping: Assessment of Patients' and Clinicians' Views on Decisional Needs We conducted key informant interview of 29 PrEP-eligible Black patientsdifferent gender, sexual orientation, and at different decision-making stage -to understand their decision-making process and to assess their decision support needs for PrEP. The result of this phase of the development process has been reported by Ajiboye et al (12). We also surveyed 25 PrEP providers (clinical and service providers) to assess needs and preferences for a decision support tool for PrEP-eligible Black patients.…”
Section: Original Manuscriptmentioning
confidence: 90%
“…The goal is to reduce decision conflict for Black patients, promote evidence-based decision on PrEP, and enhance implementation of the chosen HIV prevention option. For the providers' survey, we found that most providers ( 93% ) agreed that a decision support tool will complement the service they provide to their PrEPeligible Black patients (12). They identified Black patients' need for culturally appropriate information on the benefits and risks of PrEP as one of the reasons why a decision support tool would be needed.…”
Section: 32: Development Of the Prototypementioning
confidence: 99%
See 3 more Smart Citations